Agronomic evaluation of quinoa intercropped with coffee at an altitude of 1,800 m a.s.l. - Anchico-Jojoa, Wilson; Montes-Rojas, Consuelo; Mosquera-Chacón, Andrea; Samboni-Zemanate, Dayana Maryid (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Quinoa (Chenopodium quinoa) exhibits great potential for adaptation to various agroecological conditions, making it a diversification option for different production systems. In this regard, the objective of this study was to evaluate and compare the agronomic characteristics of different progenies intercropped with coffee (Coffea arabica) cultivation under Popayan (Colombia) conditions, in order to determine their adaptation potential in coffee regions of Colombia. The research was conducted at the Experimental Farm "La Prosperidad", located in the municipality of Popayan, Colombia, at an altitude of 1,800 m. Ten genotypes were evaluated: five selected from BRS Syetetuba (Brazil), three from Colombia (San José, Aurora, and Blanca Dulce de Jericó), and two from Ecuador (Piartal and Tunkahuan). The planting was done between the coffee rows in the zoca stage, in an experimental area of 406 m2, following a completely randomized block design with four replications. Characteristics such as plant height, panicle size, central panicle perimeter, weight of 1,000 grains, grain yield, dry mass yield, harvest index, and phenological stages were evaluated. All quinoa materials showed an early cycle with a maximum value of 118 days, with ‘San José’, ‘Aurora’, ‘BCX1’, and ‘BCX4’ standing out with averages below 110 days. Grain yields ranged from 1,120 to 2,900 kg ha-1, with the genotype BCX6 standing out with 2,900 kg ha-1 and ‘Piartal’ with 2,883 kg ha-1. The weight of 1,000 grains averaged 2.62 g, and the harvest index was 27.96%. Meanwhile, the contribution of dry matter to the intercropped system was 7,799.50 kg ha-1. The genotypes showed adaptation potential in the intercropping system with coffee. A high variability of quinoa genotypes was observed, which is an interesting characteristic for specific selection processes in diversified production arrangements.